Анализ свободных крутильных колебаний силовых передач методом нелинейных нормальных форм Шоу-Пьера - Успенский, Б. В.; Аврамов, К. В. (НТУ "ХПИ", 2014)
В статье предложена модификация метода нелинейных нормальных форм Шоу-Пьера для исследования механических систем с кусочно-линейными упругими характеристиками. Такая модификация позволяет вдвое снизить размерность системы обыкновенных уравнений, используемой для расчета форм, увеличивая таким образом точность и быстродействие метода. Рассмотрены механические системы с двумя степенями свободы, которые описывают колебания элементов силовой передачи трехцилиндрового транспортного двигателя.

Piecewise linear systems of differential equationsmodel various technological processes. Such systems are commonly used to model dynamics of systems with clearances, flexible couplings, gear trains and splined connections. Piecewise linear systems show complex dynamical behavior. A problem of obtaining Shaw-Pierre nonlinear normal modes for piecewise linear systems is considered in the paper. A modification of the Shaw-Pierre normal modes technique is suggested to half the number of corresponding algebraic equations. Efficiency of the method is demonstrated using a mathematical model of torsional oscillations of a power transmission in a triplex transport engine. Bilinear and symmetric trilinear types of elastic force are considered. A conclusion about connection between Shaw-Pierre and Rosenberg nonlinear normal modes has beenmade. Results of form calculations are numerically verified by comparing with expected system dynamics.
Using Pierre-Shaw nonlinear normal modes for analysis of free torsional oscillations in power transmissions
Keywords: система кусочно-линейная; модификация; система механическая; точность; быстродействие; двигатель; nonlinear normal modes; piecewise linear system; torsional oscillations; free oscillations; power transmission